Differential Glucose Uptake in Quadriceps and Other Leg Muscles During One-Legged Dynamic Submaximal Knee-Extension Exercise - Kalliokoski, Kari; Boushel, Robert; Langberg, Henning; Scheede-Bergdahl, Celena; Ryberg, Ann K.; Doessing, Simon; Kjaer, Andreas; Kjaer, Michael (Frontiers in Physiology, 2011)
One-legged dynamic knee-extension exercise (DKE) is a widely used model to study the local cardiovascular and metabolic responses to exercise of the quadriceps muscles. In this study, we explored the extent to which different muscles of the quadriceps are activated during exercise using positron emission tomography (PET) determined uptake of [18F]-fluoro-deoxy-glucose (GU) during DKE. Five healthy male subjects performed DKE at 25 W for 35 min and both the contracting and contralateral resting leg were scanned with PET from mid-thigh and distally. On average, exercise GU was the highest in the vastus intermedius (VI) and lowest in the vastus lateralis (VL) (VI vs VL, p<0.05), whereas the coefficient of variation was highest in VL (VL vs VI, p<0.05). Coefficient of variation between the mean values of the four QF muscles in the exercising leg was 35±9%. Compared to mean GU in QF (=100%), GU was on average 73% in VL, 84% in rectus femoris, 115% in vastus medialis, and 142% in VI. Variable activation of hamstring muscles and muscles of the lower leg was also observed. These results show that GU of different muscles of quadriceps muscle group as well as between individuals vary greatly during DKE, and suggests that muscle activity is not equal between quadriceps muscles in this exercise model. Furthermore, posterior thigh muscles and lower leg muscles are more active than hitherto thought even during this moderate exercise intensity.